Effect of post flowering foliar sprays of nutrients on fruit growth of kokum (Garcinia indica Choisy) - V S Dandekar, A V Somavanshi, P M Haldankar, (Journal of Spices and Aromatic Crops, 2012)
A study was undertaken at Dapoli (Maharashtra) to find out the effect of application of postflowering foliar nutrients on growth of kokum (Garcinia indica Choisy) fruits. Various concentrations and combinations of urea 1.0%, potassium nitrate 3.0%, monopotassium phosphate 0.5% and 19 N:19 P:19 K (1.0%) were applied at fruit set and repeated 20 days after fruit (DAF) set. The results indicated that weight of fruit increased consistently up to 90 days of fruit set and decreased slightly at harvest irrespective of treatments. The increase in fruit length and fruit circumference was linear till harvest. All foliar nutrient treatments improved the growth rate over control with respect to fruit weight, fruit length and fruit circumference at all stages of fruit growth. T4 [potassium nitrate 3.0% twice], T5 [potassium nitrate 3.0% + monopotassium phosphate 0.5%] and T6 [19 N: 19 P:19 K (1.0%) twice] were at par with each other and recorded significantly higher yield over control. Among the treatments T2 [Urea 1.0% + potassium nitrate 3.0%] was the best for improvement in fruit weight and fruit circumference of kokum fruit. All foliar nutrient sprays improved the quality of kokum fruit with respect to total soluble solids, acidity, ascorbic acid and sugar content. Among the treatments, T4 and T5 were at par with each other and significantly improved acidity and sugar content.